Netherton syndrome - Dragoš, Vlasta (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
The authors present the case of a boy with a typical Netherton syndrome (NS). In the first year of life his skin appeared erythrodermic and he suffered fromhypernatremic dehydration and failure to thrive, as well as from several bacterial infections without impaired cellular or humoral immunodeficiency. Total IgE and IgE specific for cow milk were elevated, but his condition did not improve in spite of a strict diet. After the first year of life erythroderma slowly disappeared and migratory circinate plaques typical of ichthyosis linearis circumflexa (ILC) became evident. Histopathology of skin revealed psoriasiform changes. At the age of five, eczematoid skin lesions appeared in the flexural areas, and an atopic dermatitis was additionally diagnosed. At that time total IgE levels were elevated and allergy to house mite, grass pollen, and tree pollen was found. Ultrastructural analysis of hair showed pili torti. To all above-mentioned findings the diagnosis of a NS was made. To our knowledge this is the first report of NS where the atopy was evidently manifested with atopic dermatitis.
Keywords: Anatomy and histology; Child; Dehydration; Dermatitis, atopic; dermatologija; Diagnosis; Ichthyosiform erythroderma, congenital; Ichthyosis, lamellar; IgE; kožne bolezni; Psoriasis; Skin; Therapy